Intensification of drying process during activated carbon regeneration - Atamanyuk, Volodymyr; Huzova, Iryna; Gnativ, Zoriana (Lviv Politechnic Publishing House, 2018)
Досліджено тепломасообмінний процес під час регенерації активованого вугілля. Обґрунтовано механізм фільтраційного висушування активованого вугілля за умов однакової його температури з тепловим агентом. Згідно обґрунтованому механізму, тепловому балансу та критеріальних рівнянь встановлено час припинення подачі теплового агенту. Доведено, що енергії акумульованої частини висушеного шару активованого вугілля буде достатньо для довисушування шару до кінцевої вологості. Запропонований спосіб регенерації дає змогу зменшити кількість затраченої питомої енергії.

Heat-mass exchange processes during regenerated activated carbon drying was studied to determine the minimum height of heat-mass exchange zone and termination time of hot heating agent supply based on criterion equations and heat balance calculations. The heating agent temperature changes with time and the adsorbent bed height, as well as the time of moisture content change and drying rate were studied experimentally. Minimum height of a wet material layer ensuring rational use of the heating agent was determined. Heat amount which can be saved and amount of the energy accumulated by a part of the adsorbent bed for further drying were calculated. Regeneration method allows to reduce the amount of consumed specific energy.
Інтенсифікація процесу висушування під час регенерації активованого вугілля
Keywords: адсорбент; висушування; охолодження; температурний режим; теплова енергія; зона тепло- масоперенесення; adsorbent; drying; cooling; temperature regime; heat energy; heat-mass transfer zone